Burden and factors associated with schistosomiasis and soil-transmitted helminth infections among school-age children in Huambo, Uige and Zaire provinces, Angola - Adam W. Bartlett; Jose C. Sousa-Figueiredo; Roelofje C. van Goor; Paul Monaghan; Warren Lancaster; Rukaaka Mugizi; Elsa P. Mendes; Susana Vaz Nery; Sergio Lopes (Infectious Diseases of Poverty, 2022)
Abstract Background Schistosomiasis and soil-transmitted helminths (STHs) contribute high disease burdens amongst the neglected tropical diseases (NTDs) and are public health problems in Angola. This study reports the prevalence, intensity and risk factors for schistosomiasis and STH infection in Huambo, Uige and Zaire provinces, Angola, to inform a school-based preventive chemotherapy program. Methods A two-stage cluster design was used to select schools and schoolchildren to participate in parasitological and water, sanitation and hygiene (WASH) surveys across Huambo, Uige, and Zaire provinces. Point-of-care circulating cathodic antigen and urinalysis rapid diagnostic tests (RDTs) were used to determine the prevalence of Schistosoma mansoni and S. haematobium, respectively. Kato-Katz was used to identify and quantify STH species and quantify and compare with RDTs for S. mansoni. Urine filtration was used to quantify and compare with RDTs for S. haematobium. Descriptive statistics were used for prevalence and infection intensity of schistosomiasis and STH infection. Performance of RDTs was assessed through specificity and Cohen’s Kappa agreement with microscopy. A multivariate regression analysis was used to determine demographic and WASH factors associated with schistosomiasis and STH infection. Results A total 575 schools and 17,093 schoolchildren participated in the schistosomiasis survey, of which 121 schools and 3649 schoolchildren participated in the STH survey. Overall prevalence of S. mansoni was 21.2% (municipality range 0.9–74.8%) and S. haematobium 13.6% (range 0–31.2%), with an overall prevalence of schistosomiasis of 31.4% (range 5.9–77.3%). Overall prevalence of Ascaris lumbricoides was 25.1% (range 0–89.7%), hookworm 5.2% (range 0–42.6%), and Trichuris trichiura 3.6% (range 0–24.2%), with an overall prevalence of STH infection of 29.5% (range 0.8–89.7%). Ecological zone and ethnicity were factors associated with schistosomiasis and STH infection, with older age and female sex additional risk factors for S. haematobium. Conclusions Most municipalities met World Health Organization defined prevalence thresholds for a schistosomiasis preventive chemotherapy program. A STH preventive chemotherapy program is indicated for nearly all municipalities in Uige and select municipalities in Huambo and Zaire. The association between ecological zone and ethnicity with schistosomiasis and STH infection necessitates further evaluation of home and school environmental, sociodemographic and behavioural factors to inform targeted control strategies to complement preventive chemotherapy programs.